Does wearing facial masks increase perceived facial attractiveness? An eye-tracking experiment - Jeong, Nan-Hee; Lee, Junsik; Yun, Ji-Chan; Park, Do-Hyung; Park, Se-Bum (Frontiers in Psychology, 2023)
As wearing a mask has become a routine of daily life since COVID-19, there is a growing need for psycho-physiological research to examine whether and how mask-fishing effects can occur and operate. Building upon a notion that people are likely to utilize information available from the facial areas uncovered by a mask to form the first impression about others, we posit a curvilinear relationship between the amount of the facial areas covered by a mask and the perception of others’ attractiveness such that the attractiveness perception increases initially and then decreases as more facial areas are covered by a mask. To better examine this covering effect, we conduct an experiment using an eye-tracker and also administer a follow-up survey on the facial attractiveness of target persons. Our results showed that the facial attractiveness of target persons increased as the areas covered by a mask increased as in the moderate covering condition where the target persons wore only a facial mask, demonstrating that the mask-fishing was indeed possible thanks to the covering effect of a mask on the facial attractiveness. The experimental results, however, revealed that the mask-fishing effect disappeared as the areas covered increased further as in the excessive covering condition where the target persons’ face and forehead were covered with a mask and a bucket hat. More importantly, the eye-tracking data analysis demonstrated that both the number of gaze fixation and revisits per unit area were significantly lower in the moderate covering than in the excessive covering condition, suggesting that participants in the moderate covering were able to form the impression about the target persons using cues available from the eyes and forehead areas such as hairstyle and eye color whereas those in the excessive covering were provided only a limited set of cues concentrated in the eyes area. As a result, the covering effect no longer existed under the excessive covering. Furthermore, our results showed that participants in the moderate covering were more likely than those in the excessive condition to exhibit the higher level of curiosity and perception of beautifulness but perceived the lower level of coldness when evaluating the target persons. The current research offers theoretical contributions and practical implications made from the eye-tracking experiment and discusses possible avenues for further research.